Mystical Uniquenesses and Interpretations of Qazi Sanaullah Panipati:In the Light of Tafseer e Mazhari: قاضی ثناءاللہ پانی پتی رحمۃاللہ علیہ کےصوفیا نہ تفرّدات و توجیہات: تفسیر مظہری کی روشنی میں - Hafiz Farooq, Dr.; Zia Qazi, Dr. Mohsan; Anwarullah, Dr.; Ali, Sarfraz (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Qazi Sannaullah pani patti is one of the prominent figure in learned personalities of the Sub Continent. He is also a great sofi. He gained his spiritual and selfpurification education and guidanes from sufia of tasawwuf. He did alot of work in different fields and areas of Islam. He was a great messenger of the Shaikh Mujaddid’s thoughts. He was spirtual follower of Mirza Mazhar Jan-e-jana, who was the great leader of movement of Shaikh Mujaddid. His tafseer Mazhri has a great importance in tafaseer. The following article shows the spirtual educational and practical life of Qazi Sanaullah Pani Patti.